Time From Uterine Incision to Fetal Delivery in Caesarean Sections and Neonatal Outcome - Asifa Alia, Maria Hussain, Nusrat Manzoor, Tabassum Firdous, Sadaf Saher, Zunaira Bajwa (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to evaluate the factors that influence the period from when the skin incisions are made to delivery and to identify the influence that these surgical intervals have on the immediate neonatal outcome. Study Design: This will be a prospective cohort study Place of Study: Doctors Trust Teaching Hospital Sargodha Duration of Study: December 2020 to April 2022 Materials and Methods: Tachypnea, persistence for at least 12 hours, one of the chest X-ray abnormalities, and elimination of other respiratory or non-respiratory illnesses helped the paediatric team diagnose TTN. Tachypnea produces fast, shallow breathing. These criteria diagnosed TTN. Tachypnea within six hours of delivery, persistence for at least twelve hours, a chest X-ray abnormality, and elimination of other respiratory or non-respiratory illnesses were the criteria. Result: There was a correlation between the development of TTN and the demographic age (GA), which was statistically significant; however, there was no correlation between the development of TTN and any of the other parameters that were evaluated. There was no evidence to suggest that any of the other risk factors that were investigated were significantly linked with the development of TTN. Practical Implication: Correlation between the development of TTN and the demographic age (GA), but no correlation between the development of TTN and any of the other parameters that were evaluated Conclusion: The authors have concluded that there is no association between TTN and the time between the beginning of the surgical procedure and the delivery of the baby when the patient is under spinal anaesthesia. They argue for the importance of research with larger populations to determine the safest time limit for the delivery of foetal tissue and other potential risks associated with the development of TTN. Keywords: Caesarean section, Decision to delivery interval, Feto-maternal outcome